2018
DOI: 10.4103/abr.abr_187_17
|View full text |Cite
|
Sign up to set email alerts
|

Postmastectomy Information Needs and Information-seeking Motives for Women with Breast Cancer

Abstract: Background:Health information-seeking behavior is a key concept in the empowerment of women with breast cancer after mastectomy for self-care management. Thus, a real understanding of their information needs and their information-seeking behavior may open up new opportunities for their postsurgery cares. The current research was conducted to identify the information needs and information-seeking motives of women with breast cancer after mastectomy.Materials and Methods:This is an applied qualitative research. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 22 publications
(30 reference statements)
0
28
0
1
Order By: Relevance
“…Three studies reported that patients were concerned about information on prevention, including effectiveness of breast self-examination [ 40 ] in phase 2. Patients reported that they also needed information about prevention for family members [ 30 , 42 , 43 ] during the survivorship stage.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Three studies reported that patients were concerned about information on prevention, including effectiveness of breast self-examination [ 40 ] in phase 2. Patients reported that they also needed information about prevention for family members [ 30 , 42 , 43 ] during the survivorship stage.…”
Section: Resultsmentioning
confidence: 99%
“…For example, patients wanted to know about internal and external factors (risk factors) before diagnosis in phase 1 [ 36 ] and phase 2 [ 40 ]. Patients also needed information on internal (genetic) [ 42 , 44 ] and external factors (possible carcinogens and environmental triggers) [ 44 ] in the survivorship stage in phase 3.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Una mayor malestar con la imagen corporal tras la mastectomía se asocia a una disposición motivacional más favorable hacia la reconstrucción, más motivos a favor de la reconstrucción y menor aceptación del estado actual tras la mastectomía, lo que confirma reportes previos (20,47) y da validez a las escalas. Asimismo, las mujeres con más conflictos con su imagen post-mastectomía son las que se quejan de más falta de información como refleja la correlación positiva entre el CIC y el tercer factor de la EMEC.…”
Section: Discussionunclassified